The adaptor protein 14-3-3 binds to the calcium-sensing receptor and attenuates receptor-mediated Rho kinase signalling - Arulpragasam, Ajanthy; Magno, A.; Ingley, E.; Brown, S.; Conigrave, A.; Ratajczak, T.; Ward, B. (2012)
A yeast two-hybrid screen performed to identify binding partners of the CaR (calcium-sensing receptor) intracellular tail identified the adaptor protein 14-3-3? as a novel binding partner that bound to the proximal membrane region important for CaR expression and signalling. The 14-3-3? protein directly interacted with the CaR tail in pull-down studies and FLAG-tagged CaR co-immunoprecipitated with EGFP (enhanced green fluorescent protein)-tagged 14-3-3? when co-expressed in HEK (human embryonic kidney)-293 or COS-1 cells. The interaction between the CaR and 14-3-3? did not require a putative binding site in the membrane-proximal region of the CaR tail and was independent of PKC (protein kinase C) phosphorylation. Confocal microscopy demonstrated co-localization of the CaR and EGFP-14-3-3? in the ER (endoplasmic reticulum) of HEK-293 cells that stably expressed the CaR (HEK-293/CaR cells), but 14-3-3? overexpression had no effect on membrane expression of the CaR. Overexpression of 14-3-3? in HEK-293/CaR cells attenuated CaR-mediated Rho signalling, but had no effect on ERK (extracellular-signal-regulated kinase) 1/2 signalling. Another isoform identified from the library, 14-3-3?, exhibited similar behaviour to that of 14-3-3? with respect to CaR tail binding, cellular co-localization and impact on receptor-mediated signalling. However, unlike 14-3-3?, this isoform, when overexpressed, significantly reduced CaR plasma membrane expression. Results indicate that 14-3-3 proteins mediate CaR-dependent Rho signalling and may modulate the plasma membrane expression of the CaR. © The Authors Journal compilation © 2012 Biochemical Society.